Lysine Acetylation in the Proteome of Renal Tubular Epithelial Cells in Diabetic Nephropathy - Wan, Jiayi; Hu, Mingyang; Jiang, Ziming; Liu, Dongwei; Pan, Shaokang; Zhou, Sijie; Liu, Zhangsuo (Frontiers in Genetics, 2021)
Diabetic nephropathy is considered as one of the most common microvascular complications in diabetic patients and involves multiple factors. Progressive diabetic nephropathy is believed to be related to the structure and function of the tubular epithelial cells in the kidney. However, the role of lysine acetylation in lesions of the renal tubular epithelial cells arising from hyperglycemia is poorly understood. Consequently, in this study, we analyzed the acetylation of proteins in the proximal renal tubular epithelial cells of mice under high glucose conditions by high resolution liquid chromatography-tandem mass spectrometry. We identified 51 upregulated proteins and downregulated 87 proteins. In addition, we identified 186 sites with higher acetylation levels and 464 sites with lower acetylation levels. The majority of the acetylated proteins were found primarily in the mitochondria (36.28%), nucleus (30.93%), and cytoplasm (19.30%). Enrichment analysis indicated that these acetylated proteins are primarily associated with oxidative phosphorylation, the tri-carboxylic acid (TCA) cycle, nucleoside phosphate metabolic processes, and fatty acid degradation. In addition, we used the STRING database and Molecular Complex Detection (MCODE) software and identified four MCODES and 10 hub genes from differential proteome and acetylation differential proteome respectively. Finally, we extracted 37 conserved motifs from 4915 acetylated peptides. Collectively, these data provide novel insights for the role of lysine acetylation in tubular epithelial cells in diabetic nephropathy.